KESTABILAN HABITAT LAMUN DITINJAU DARI KOMPOSISI DAN KEPADATAN JENIS - Paskalina Th. Lefaan (FMIPA Universitas Papua, 2009)
Seagrasses habitats have both physical and ecological functions that support adjacent waters qualities and its dwelling organisms. There are varies of pressure on seagrass environmental, especially due to people activities that could decrease its function and habitat stabilities. The study aimed to determine about seagrass habitat stabilities from its species composition and/or densities. Line transect-plots and exploration methods were used in five locations of Manokwari coastal waters, that were, Andai, Rendani, Wosi, Briosi, and Tanjung Manggewa. There are five pioneer species (Cymodocea rotundata, Halodule pinifolia, H. uninervis, Syringodium isoetifolium, Halophila ovalis) and 3 climax species (Cymodocea serrulata, Enhalus acoroides, Thalassia hemprichii). The pioneer only found in Andai and Wosi, however both pioneer and climax encountered in three other locations. In Rendani and Tanjung Manggewa higher density of climax species (T. hemprichii) were 617.7 and 828.0 stands m-2, respectively, although in Briosi the higher pioneer (C. rotundata) of 570.7 stands m-2. These conditions showed that seagrass habitat in Rendani and Tanjung Manggewa are more stable compared to Briosi, as well as Andai and Wosi. It concluded that pioneer species found in newly formed habitat or disturbed, on the other hand, climax in more stable habitat.